MORPHOLOGICAL CHARACTERISTICS OF KUSCHAKEWITSCH LOACH FROM THE GREAT FERGANA CANAL AND CHADAKSAY RIVER (Scientific journal of the Fergana State University, 2024)
Kuschakewitsch loach — Iskandaria kuschakewitschi (Herzenstein, 1890) is an endemic of the Fergana Valley and occurs in the Karadarya, Syrdarya, Margilansay, Isfayramsay, Chodaksay rivers and other various water bodies. Due to morphologically wide plasticity, some differences in its morphometric properties are observed in various water bodies. This article compares and analyzes the morphological, morphometric and meristic parameters of Kuschakewitsch loach in the Great Fergana Canal and Chodaksay River. The study of the morphological variability of fish in different water bodies is important for the correct species identification, as well as, for understanding the process of intraspecific differentiation.